ASSESSMENT OF WATER QUALITY REMEDIATION THROUGH AQUAPONIC SYSTEMS - Van Quang, Nguyen; The Hung, Nguyen; J Wu, Jerry (Journal of Forestry Science and Technology, 2019)
Research records data related to small-scale aquaponic systems were applied using two pilot models, Floating bed systems (FBS) and Media Filled Systems (MFS), for effective testing as well as assessment. Aquaponic is a sort of bioreactor that combines the process of fish farming and use of plants to recycle wastewater, which is the combination of aquaculture and hydroponics. The physics chemical parameters, such as DO, pH, temperature, COD, BOD5, NO2-N, NO3-N, NH3-N and PO4-P, were evaluated in each system over a period of 75 days. In the Media filled systems (MFS) water quality parameters were reduced for 75 days DO, pH, BOD, COD, NO2-N, NO3-N, NH3-N, and PO4-P is 7.0 mg/L, 7.31, 4.66 mg/L, 6.86 mg/L 1.31 mg/L, 1.1 mg/L, 1.42 mg/L, and 0.41 mg/L and Floating bed systems (FBS) were also shown DO, pH, BOD, COD, NO2-N, NO3-N, NH3-N, and PO4-P were 6.88 mg/l, 7.46, 4.81 mg/L, 6.88 mg/L, 1.95 mg/L, 1.47 mg/L, 1.48 mg/L, 0.48 mg/L. The average weight of fish is 30 grams which is 40% higher than the original weight, average yield of 45.5 grams per plants showed that the system yielded satisfactory results. Two systems are effective in improving water quality. However, in MFS system is more efficient than the FBS system.